The factors influence to reduce the cost for implementing industrialized building system (IBS) in Malaysia - Siti Aisah, Abu Bakar (2018)
IBS is a construction system using pre-fabricated components. The manufacturing of the components is systematically organize using machine, formworks and other forms of mechanical equipment. The components are manufactured in the factory and once completed will be delivered to construction sites for assembly and erection. However, the implementation of IBS in the construction industry is still low which represents only about 15-20 per cent of the overall projects in Malaysia. There are three (3) main objectives of this research such as to study about IBS method for construction in Malaysia, to identify the factors that can reduce the cost of implementation of IBS in Malaysian construction industry and to analyse the most prominent factor that can reduce the cost of implementation IBS in Malaysian construction industry. Questionnaires survey was conducted in order to obtain the objective. The respondents for answering the questionnaires consist of person who involved of construction project. The data were tabulated using Microsoft Excel and then analysed using Average Index method. Based on the past reviews of research and related literature, there were five (5) factors that can reduce the cost for IBS implementation that classified as prices of building materials, labour, government support, productivity and technology. In conclusion, the most prominent factor to reduce the cost for IBS implementation in Malaysia is productivity. IBS construction will save valuable time and help to reduce the risk of project delay and possible monetary losses. The design and production of IBS elements can begin while the construction site is still under survey or at earthwork phase.